Komunikasi Pembangunan Dalam Mencapai Supremasi Hukum Meninjau Kasus Waduk Jatigede Terkait SDGs No. 16 - Wicaksana, Dika Hikmah; Ramadhan, Niko Rafael; Ramadhan, Aditya Rizky; Winata, Henry; Asri, Muh Rozi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research analyzes Development Communication in the case of the construction of the Jatigede Reservoir regarding the Supremacy of Law in the Perspective of Sustainable Development Goals Number 16. The research method used is a literature review technique with a normative juridical approach. The research results show that in the Jatigede Reservoir construction case there were legal disagreements and imbalances between the majority of the local community and the government under the pretext of national development which resulted in legal coverage. This second case shows that the failure to achieve the rule of law for affected victims also maintains the importance of the role of development communication in order to support community awareness and empowerment.